The treatment of diffuse cutaneous systemic sclerosis with autologous hemopoietic stem cells transplantation (HSCT): our experience on 2 cases - A. Tyndall; S. Urbani; S. Guidi; A. Bosi; S. Guiducci; F. Pagliai; R. Saccardi; I. Miniati; M. Matucci Cerinic (PAGEPress Publications, 2011)
Objectives: Autologous hematopoietic stem cell transplantation (HSCT) is a treatment option which may be considered for severe diffuse cutaneous systemic sclerosis (dcSSc) patients not responding to cyclophophamide (CY). We present two cases of dcSSc not responding to CY >10 g who were successfully treated with HSCT. Patients and methods: Two dcSSc patients were unresponsive to monthly i.v. pulse of CYC (0.75 g m2). Both patients had significant reduction of DLCO and mild-moderate pulmonary hypertension and HSCT was considered due to the rapid progression of the disease. Following informed consent and ethics committee approval, HSCT was performed. Mobilisation was performed with CY 4g/m2 and recombinant human granulocyte colony stimulating factor (rHu GCSF) followed by a successful apheresis (CD34+ cells, >7X106). Conditioning regimens were: CY 100mg/kg body weight plus thiotepa 10 mg/ kg in the first patient and CY 200 mg/kg in the second. Both graft products were CD34 selected. No arrythmias occurred during the procedure and no other severe side effects were observed during hospitalisation. Results: Follow up: Patients underwent a monthly follow up with physical examination, pulmonary function tests and echocardiography every 3 months. Chest CT has been performed 6 months post transplantation. The following was observed: skin score (from 40 to 10 for the first patient and from 38 to 12 for the second one), LVEF and pulmonary function remained stable, PAP decreased from 45 mmHg to 35 mmHg and from 40 to 32 mmHg. No late complications or cardiac toxicity was observed. Conclusion: These two dcSSc cases demonstrate that HSCT may be successfully performed without serious side effects in cases in whom despite a cumulative CY dose was ineffective. This suggests an "immunological threshold" effect which may be exploited in other severe, therapy refractory autoimmune cases.